2021
DOI: 10.1002/elan.202100361
|View full text |Cite
|
Sign up to set email alerts
|

A New Chemically Modified Carbon Paste Electrode Derived from Aloe Vera Xanthate Nanoparticles to Detect Mercury Ions

Abstract: This environmentally benign work describes a simple electrochemical sensor constructed with a chemically modified carbon paste electrode (CMCPE) using aloe vera xanthate nanoparticles to detect mercury ions. The characterization and morphology of nanoparticles were thoroughly investigated using modern techniques. The CMCPE efficiently senses the mercury ions. The limit of detection of mercury ions wasexcellent to the order of 0.231 μg mL−1. Real‐time sample analysis showed promising results. The recovery range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The contribution of CPy to the current value was clearly seen, as a rapid increase in the current value was observed after the 0.8 V potential. Nyquist curves of CPE/PANI/INV‐GOD and CPE CPy /PANI/INV‐GOD electrodes obtained by applying 0.60 V potential with 4 mV amplitude in the frequency range of 10 5 –10 −3 Hz in sucrose‐free and sucrose‐containing buffer solutions revealed that the transfer rates were higher in sucrose solution than those of sucrose‐free buffer (Figure 8B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of CPy to the current value was clearly seen, as a rapid increase in the current value was observed after the 0.8 V potential. Nyquist curves of CPE/PANI/INV‐GOD and CPE CPy /PANI/INV‐GOD electrodes obtained by applying 0.60 V potential with 4 mV amplitude in the frequency range of 10 5 –10 −3 Hz in sucrose‐free and sucrose‐containing buffer solutions revealed that the transfer rates were higher in sucrose solution than those of sucrose‐free buffer (Figure 8B).…”
Section: Resultsmentioning
confidence: 99%
“…CPE, the most basic component of graphite and a binder, has very different usage potentials due to its modification of both the paste content and the electrode surface. In the literature, several studies are reported about the composition of the paste and its modification with metal or metal oxide nanoparticles (NPs), CNT or MWCNT, ionic liquids, organic compounds, and polymeric composites 2–5 . Moreover, studies in which the electrode surface is modified with polymers such as nafion, 6 polyaniline (PANI), poly(1.3‐phenylenediamine), 7 chitosan, 8,9 or composite materials such as CuO nanoflower, 10,11 gold NP–chitosan/graphen, 12 nano‐Au particle–decorated poly(3‐amino‐5‐hydroxypyrazole) 13 are carried out.…”
Section: Introductionmentioning
confidence: 99%
“…They have found diverse applications in science and technology, including cellular imaging, chemical sensing, biochemical sensing, and electrical conductivity 25 33 . Various synthesis methods, such as chemical oxidation 34 , hydrothermal processes 35 37 , microwave-assisted techniques 38 , and electrochemical approaches 39 , have been employed using organic compounds as precursors. However, these methods often suffer from drawbacks such as high energy consumption, complex processing steps, uncontrollable reactions, the use of corrosive chemicals, and limited commercial feasibility 40 .…”
Section: Introductionmentioning
confidence: 99%